A case of Multisystem Inflammatory Syndrome in Children (MIS-C) (Anwer Khan Modern Medical College Journal, 2023)
Multisystem inflammatory syndrome in children (MIS-C) is a systemic disorder involving persistent fever, extreme inflammation and organ dysfunction, which is temporally associated with exposure to COVID-19. onset may be delayed or contemporary with ongoing SARS-CoV-2 infection. Here we present a case of 4-year-old girl, who was presented with high grade fever, bilateral non-purulent conjunctivitis, generalized macular rash, dry and cracked lips with strawberry tongue, abdominal pain and diarrhoea, having contact with patient of COVID-19. She had neutrophilic leukocytosis with thrombocytosis and very high inflammatory markers, CXR demonstrated bilateral peripheral patchy opacities, RT-PCR for COVID-19 was negative. According to diagnostic criteria this patient was diagnosed as Multisystem inflammatory syndrome in children (MIS-C) which is temporally associated with COVID-19 and treated successfully.AKMMC J 2021; 12(1) : 62-65